Excess gestational weight gain: an exploration of midwives' views and practice - Willcox Jane C; Campbell Karen J; van der Pligt Paige; Hoban Elizabeth; Pidd Deborah; Wilkinson Shelley (BMC, 2012)
Abstract Background Excess gestational weight gain (GWG) can affect the immediate and long term health outcomes of mother and infant. Understanding health providers' views, attitudes and practices around GWG is crucial to assist in the development of practical, time efficient and cost effective ways of supporting health providers to promote healthy GWGs. This study aimed to explore midwives' views, attitudes and approaches to the assessment, management and promotion of healthy GWG and to investigate their views on optimal interventions. Methods Midwives working in antenatal care were recruited from one rural and one urban Australian maternity hospital employing purposive sampling strategies to assess a range of practice areas. Face-to-face interviews were conducted with 15 experienced midwives using an interview guide and all interviews were digitally recorded, transcribed verbatim and analysed thematically. Results Midwives interviewed exhibited a range of views, attitudes and practices related to GWG. Three dominant themes emerged. Overall GWG was given low priority for midwives working in the antenatal care service in both hospitals. In addition, the midwives were deeply concerned for the physical and psychological health of pregnant women and worried about perceived negative impacts of discussion about weight and related interventions with women. Finally, the midwives saw themselves as central in providing lifestyle behaviour education to pregnant women and identified opportunities for support to promote healthy GWG. Conclusions The findings indicate that planning and implementation of healthy GWG interventions are likely to be challenging because the factors impacting on midwives' engagement in the GWG arena are varied and complex. This study provides insights for guideline and intervention development for the promotion of healthy GWG.